2010
DOI: 10.1089/jwh.2009.1568
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Turning Points in Intimate Partner Violence: Factors and Circumstances Leading Women Victims Toward Change

Abstract: Objective: When counseling women experiencing intimate partner violence (IPV), healthcare providers can benefit from understanding the factors contributing to a women's motivation to change her situation. We wished to examine the various factors and situations associated with turning points and change seeking in the IPV situation. Methods: We performed qualitative analysis on data from 7 focus groups and 20 individual interviews with women (61 participants) with past and=or current histories of IPV. Results: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(116 citation statements)
references
References 75 publications
7
106
0
3
Order By: Relevance
“…This finding is in agreement with those in the literature showing that social support protects against the deleterious effects of IPV on women's health, increases the likelihood that women will take actions to eliminate IPV (Campbell et al, 1995;Chang et al, 2010;Coker et al, 2002;Escrib a-Ag€ uir et al, 2010;Mburia-Mwalili, ClementsNolle, Lee, Shadley, & Wei, 2010), and decreases the risk of partner revictimization (Bybee & Sullivan 2002;2005). Thus, these studies highlight the buffering effects that social support has on the impact of IPV on women's health and its beneficial effects regarding recovery from IPV over time.…”
Section: Factors That Improve Physical Healthsupporting
confidence: 92%
“…This finding is in agreement with those in the literature showing that social support protects against the deleterious effects of IPV on women's health, increases the likelihood that women will take actions to eliminate IPV (Campbell et al, 1995;Chang et al, 2010;Coker et al, 2002;Escrib a-Ag€ uir et al, 2010;Mburia-Mwalili, ClementsNolle, Lee, Shadley, & Wei, 2010), and decreases the risk of partner revictimization (Bybee & Sullivan 2002;2005). Thus, these studies highlight the buffering effects that social support has on the impact of IPV on women's health and its beneficial effects regarding recovery from IPV over time.…”
Section: Factors That Improve Physical Healthsupporting
confidence: 92%
“…This finding parallels the study outcomes of interpersonal violence research that stresses the significance of various psychological attributes (e.g., self-esteem, self-confidence, self-determination, sense of autonomy) in formulating good judgment and avoiding further abuse (e.g., Suvak, Taft, Goodman, & Dutton, 2013;Papadakaki et al, 2009). Good cognitive abilities not only increase survivors' understanding of their circumstance but can help them work through the complications they are facing (Chang et al, 2010).…”
Section: Mental Healthsupporting
confidence: 71%
“…Similarly, Chang [97] has shown that screening for IPV during pregnancy can help raise awareness and women's interactions with health care providers may help change women's perceptions. Health psychology has demonstrated that an effective means to change health related behaviour is to ask people questions about that behaviour (e.g.…”
Section: Perceived Helpfulness Of the Interventionmentioning
confidence: 99%